Tunable ballistic thermal conductance of electrons in strained graphene nanoribbons. (April 2016) - Peng, Xiao-Fang; Chen, Ke-Qiu; Wang, Xin-Jun; Tan, Shi-Hua
Abstract: The thermal transport properties of electrons in graphene nanoribbon (GNR) subjected to strain fields are studied by non-equilibrium Green's function approach. The results show that the stretching of the carbon–carbon bond in strained GNR can enhance the ballistic thermal conductance of electrons. The enhancement originates from that the change of C–C bond length can modulate the nearest-neighbour π -orbital overlap and reduce the threshold energies of electron transport modes. A brief analysis of these results is given.